Development and validation of a Chinese character acquisition assessment for second-language kindergarteners. (April 2020) - Chan, Stephanie W. Y.; Cheung, Wai Ming; Huang, Yanli; Lam, Wai-Ip; Lin, Chin-Hsi
Demand for second-language (L2) Chinese education for kindergarteners has grown rapidly, but little is known about these kindergarteners' L2 skills, with existing studies focusing on school-age populations and alphabetic languages. Accordingly, we developed a six-subtest Chinese character acquisition assessment to measure L2 kindergarteners' abilities to make associations among the forms, sounds, and meanings of 40 Chinese characters, and administered it to 173 five- and six-year-old L2 kindergarteners in Hong Kong. We found a high model-to-data fit using the two-parameter logistic item response theory model ( MS infit = .87 to 1.07, p s > .41). Of the 40 items, 36 exhibited a range of difficulty and good discrimination. Internal consistency reliability and inter-rater reliability were also high. The children scored highest in the category of meaning-sound associations, followed by mapping from meaning to form. The results demonstrate that the instrument is adequately valid and reliable for assessing L2 kindergarteners' character acquisition and imply that child L2 learners may develop abilities to map meanings and sounds prior to their development of form-related mapping. With minor modifications, the developed instrument can be used in various child Chinese L2 programs around the world.